Exercise as a prescription for patients with various diseases - Xin Luan; Xiangyang Tian; Haixin Zhang; Rui Huang; Na Li; Peijie Chen; Ru Wang (Elsevier, 2019)
A growing understanding of the benefits of exercise over the past few decades has prompted researchers to take an interest in the possibilities of exercise therapy. Because each sport has its own set of characteristics and physiological complications that tend to occur during exercise training, the effects and underlying mechanisms of exercise remain unclear. Thus, the first step in probing the effects of exercise on different diseases is the selection of an optimal exercise protocol. This review summarizes the latest exercise prescription treatments for 26 different diseases: musculoskeletal system diseases (low back pain, tendon injury, osteoporosis, osteoarthritis, and hip fracture), metabolic system diseases (obesity, type 2 diabetes, type 1 diabetes, and nonalcoholic fatty liver disease), cardio-cerebral vascular system diseases (coronary artery disease, stroke, and chronic heart failure), nervous system diseases (Parkinson's disease, Huntington's disease, Alzheimer's disease, depression, and anxiety disorders), respiratory system diseases (chronic obstructive pulmonary disease, interstitial lung disease, and after lung transplantation), urinary system diseases (chronic kidney disease and after kidney transplantation), and cancers (breast cancer, colon cancer, prostate cancer, and lung cancer). Each exercise prescription is displayed in a corresponding table. The recommended type, intensity, and frequency of exercise prescriptions are summarized, and the effects of exercise therapy on the prevention and rehabilitation of different diseases are discussed. Keywords: Diseases, Exercise prescription, Patients